Effect of risperidone on plasma vascular endothelial growth factor levels in patients with first-episode schizophrenia: A preliminary study - Reiji Yoshimura; Naomichi Okamoto; Gaku Hayasaki; Issei Seki; Reoto Kijima; Enkmurun Chibaatar; Atsuko Ikenouchi (Psychiatry Research Communications, 2023)
This study investigated the role of vascular endothelial growth factor (VEGF) in 18 patients with first-episode schizophrenia (FES) and 19 healthy controls and the effect of risperidone monotherapy on plasma VEGF levels. The plasma VEGF levels were measured at baseline and after four weeks of risperidone treatment. We found no difference in baseline VEGF levels between the groups and no change in VEGF levels after risperidone treatment. No correlation was found between VEGF levels and symptom severity. Our findings suggest that VEGF may not serve as a distinguishing biomarker in FES or be directly influenced by risperidone.